Identification Policy: Addressing Equity and Excellence for Advanced Learners. Issue 4 (October 2022) - Plucker, Jonathan A.; Wells, April; Meyer, Melanie S.
Identification for gifted and talented services is governed by state and local policies. Inclusive, student-centered policies can support equity and excellence by ensuring that all students have access to appropriate levels of academic challenge. Gifted programming standards, evidence-based interventions, and emerging strategies can provide guidance for the creation of strong identification policies and for the revision of policies that do not adequately support equitable access, program alignment, and the proportional representation of students from culturally, linguistically, and economically diverse backgrounds. Some critical points to consider when creating identification policies for advanced learning programs include providing opportunities to learn, expanding access to advanced programming, embedding retention supports, ensuring flexibility to account for local needs, maintaining an emphasis on excellence, and inviting input from families and community members.